Pengaruh Workplace Loneliness dan Stres Kerja terhadap Kinerja Karyawan Dimediasi Nilai Spiritual Islami: Studi di Bank BNI Syariah Yogyakarta - Ulfah Sa'adah Ramadhani; Muafi Muafi (Sekolah Tinggi Ilmu Manajemen YKPN Yogyakarta, 2021)
The purpose of this study was to examine and analyze workplace loneliness and work stress on employee performance mediated by Islamic spiritual values. The research was conducted at Bank BNI Syariah Yogyakarta with a sample size of 75 respondents and using quantitative methods. The data collection technique was carried out by using a questionnaire distributed via google form, then the results of the study were analyzed statistically using SEM (structural equation modeling) with the help of SMART PLS software. The results of the study found that there was no positive and significant effect of workplace loneliness on Islamic spiritual values in employees, there was no positive and significant effect of workplace loneliness on employee performance, then there was a negative and significant effect of work stress on Islamic spiritual values, there was a negative and significant effect on work stress. On employee performance, there is no positive and significant influence of Islamic spiritual values on employee performance. In addition, Islamic spiritual values cannot significantly mediate the relationship between workplace loneliness and employee performance and show that Islamic spiritual values significantly mediate the relationship between work stress and employee performance in employees at Bank BNI Syariah Yogyakarta.